1978
DOI: 10.1007/bf00235575
|View full text |Cite
|
Sign up to set email alerts
|

Direct excitation of neck motoneurons by interstitiospinal fibers

Abstract: 1. Responses of neck motoneurons to stimulation of the interstitial nucleus of cajal (INC) were recorded intracellularly in cats under chloralose anesthesia. When stimuli were applied within or close to the INC, short latency, monosynaptic excitatory postsynaptic potentials (EPSPs) were evoked in many neck motoneurons. Such EPSPs were not evoked by stimulating mesencephalic regions outside the INC. 2. Stimulation of the ipsilateral INC produced monosynaptic EPSPs consistently in biventer cervicis-complexus (BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The nucleus reticularis gigantocellularis (NRG) and the nucleus reticularis pontis caudalis (NRPC) contain excitatory and inhibitory burst neurons that discharge during horizontal head rotations (Peterson, Pitts, Fukushima, & Mackel, 1978). Finally, the Forel's field of H (FFH) and the interstitial nucleus of Cajal discharge during vertical head rotations (Fukushima, van der Hoeff-van Halen, & Peterson, 1978;Isa, Itouji, Nakao, & Sasaki, 1988;. Thus, as for the control of the eye movement, a synchronization of different populations of neurons is necessary to generate an oblique head movement.…”
Section: Dimensionality Of the Tracking Movementmentioning
confidence: 98%
“…The nucleus reticularis gigantocellularis (NRG) and the nucleus reticularis pontis caudalis (NRPC) contain excitatory and inhibitory burst neurons that discharge during horizontal head rotations (Peterson, Pitts, Fukushima, & Mackel, 1978). Finally, the Forel's field of H (FFH) and the interstitial nucleus of Cajal discharge during vertical head rotations (Fukushima, van der Hoeff-van Halen, & Peterson, 1978;Isa, Itouji, Nakao, & Sasaki, 1988;. Thus, as for the control of the eye movement, a synchronization of different populations of neurons is necessary to generate an oblique head movement.…”
Section: Dimensionality Of the Tracking Movementmentioning
confidence: 98%
“…DN has also been associated with ves tibular induced eye movements [Szentago-lhai and Schab. 1956;Scheibel et al, 1961] and cervical motoneuron function [Fukushima et al, 1978] producing inhibition by relay in vestibular nuclei [Markham et al, 1966], reticular formation [Carpenlerel al., 1970] or in the spinal cord [NybergHansen, 1966].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study are not conclusive on this point. Fukushima et al (1978) observed that stimulation of the interstitial nucleus of Cajal result in direct excitation of neck motoneurons. However, Holstege and Cowie (1989) showed that in mammals the mesencephalic reticular formation adjacent to the interstitial nucleus of Cajal projects directly to the neck motor area in the ventral horn, but the nucleus interstitialis itself does not contribute to this projection.…”
Section: Comparison With Mammalsmentioning
confidence: 97%